Acute pain problems post surgery carcinoma mammary : a case study - Mardiah Mardiah (Journal of Midwifery and Nursing, 2023)
Carcinoma mammae or breast cancer is a disorder in irregular cell growth that becomes a lump that grows in the duct that connects the lobolus to the nipple. The purpose of the case study was to do Nursing Care for Mrs. "E" with acute pain problems post surgery carsinoma mammae in the Marwah Room of Siti Khadijah Islamic Hospital Palembang. The research method used was descriptive with a narrative case study model on April 28 – May 1, 2023. The study results with Mrs. E were patients who said pain in postoperative wounds in the upper breast and extra pain like in stabbing with a pain scale of 4 from a scale of 1-10. Physical examination blood pressure: 120/70 mmHg, pulse rate: 80 x/m, respiration rate: 20 x/m, Temperature: 360°C.     Mrs.E.'s nursing diagnosis was acute pain associated with physical injury agents (surgical procedures). The interventions were vital sign monitors, location identification, characteristics, duration, frequency, quality, pain intensity, and pain scale identification. At this stage of nursing, implementation was by the nursing plan. At the evaluation stage, after nursing actions for 4x24 hours, acute pain problems were resolved, and patients are allowed to go home by doctors. Suggestions: It was hoped that this research can be used as one of the additional information for health workers and add insight into the field of nursing science and technology.